Cross-sectional study of health impairment related to post COVID-19 condition among participants of a large population-based cohort in Germany - Diexer, Sophie; Frost, Jonas; Bärnighausen, Till; Brenner, Hermann; Gabrysch, Sabine; Greiser, Karin Halina; Kaaks, Rudolf; Klee, Bianca; Pfrommer, Laura R.; Purschke, Oliver; Mikolajczyk, Rafael (Scientific reports, 2025)
Post COVID-19 condition (PCC) is a substantial burden for patients, society, and the healthcare system. Participants of the German National Cohort (NAKO) were asked in an online survey about their self-perceived health, symptoms related to PCC, and infection status. PCC was defined as reporting symptoms for the time window 4–12 months after infection. Of 110,375 respondents (73% response), 86,833 were included in this analysis. Of these, 44,451 (51%) did not report a SARS-CoV-2 infection (no infection), 26,726 (31%) reported an infection but no symptoms 4–12 months after infection (infection/no PCC), and 15,656 (18%) reported an infection and symptoms (PCC). The median number of current symptoms at the time of the survey was two for the "no infection" and the "infection/no PCC" group, and five for the "PCC" group. Participants with PCC had a substantially higher probability of having worse self-perceived health (OR 1.84, 95% CI [1.75; 1.93] compared to the "no infection" group, adjusting for sex, age, education and chronic diseases with elevated risk for developing PCC. After adjusting for the number of current symptoms related to PCC, this difference disappeared, suggesting that the symptoms collected explain the impairment of self-perceived health in the PCC group.